myofibroblast, a key cell in normal and pathological tissue repair - Darby, Ian A; Zakuan, Noraina; Billet, Fabrice; Desmoulière, Alexis (Cellular and molecular life sciences : CMLS, 2016)
Myofibroblasts are characterized by their expression of α-smooth muscle actin, their enhanced contractility when compared to normal fibroblasts and their increased synthetic activity of extracellular matrix proteins. Myofibroblasts play an important role in normal tissue repair processes, particularly in the skin where they were first described. During normal tissue repair, they appear transiently and are then lost via apoptosis. However, the chronic presence and continued activity of myofibroblasts characterize many fibrotic pathologies, in the skin and internal organs including the liver, kidney and lung. More recently, it has become clear that myofibroblasts also play a role in many types of cancer as stromal or cancer-associated myofibroblast. The fact that myofibroblasts are now known to be key players in many pathologies makes understanding their functions, origin and the regulation of their differentiation important to enable them to be regulated in normal physiology and targeted in fibrosis, scarring and cancer.